Manajemen Stratejik Dalam Pengembangan Kultur Organisasi - Murniati AR (Jurnal Transformasi Administrasi, 2013)
Organizationisplaceorprocessinfulfillingtheneedsofindividualandorganization.Organization must own cultur that is made characteristic behavior pattern of member the organizations which aims as differentiator from other organizations, the indentity of organization, and trigger organizational members commitment. Organizational culture must be dynamic, according to the needs of internal and external organizations. Within the organizational culture needs to implement strategic management. Management strategy oriented to internal and external decision making.